ANALYSIS OF DESIGN AND IMPLEMENTATION OF INFORMATION SYSTEM OF LIBRARY OF UIN SUNAN KALIJAGA JOGYAKARTA - Hendra Junawan (UIN Sumatera Utara, 2020)
The purpose of writing this article is to find out how to design and implement the Information System of the Sunan Kalijaga State Islamic University Yogyakarta Library which is supported by the System Development Life Cycle (SDLC). The method used in this study is the type of field research that is